The climatic risks to livestock production in the Ethiopian rangelands (southern, north-eastern and Jijiga Rangeland Development Units) - Bille, Jean-Claude (International Livestock Centre for Africa, 1983)
Simplified description of total annual rainfall, monthly rainfall, annual variations & spatial distribution in the Southern, North-Eastern & Jijiga rangeland development units where livestock development efforts are under way. Measures risks associated with dif. forms of livestock production & assesses the validity of present interventions in the project against patterns & probabilities of rainfall.